Analisis Natur ke-Allahan dan Kemanusiaan Yesus Kristus dalam Teologi Perjanjian Baru - Darmianus Harefa; Adika Putri Manein (Program Studi Teologi, Fakultas Teologi, Institut Agama Kristen Negeri Manado, 2023)
This article was created with the aim of knowing and understanding the nature of Jesus Christ through analyzing His two natures, namely the nature of the Godhead and humanity in the New Testament theology. This research was conducted due to the emergence of various teachings that are not in accordance with the truth of the Word which attack sound teachings or teachings that are in accordance with the truth of the Word. This research was also carried out so that Christians can correctly understand the person of Jesus Christ in His nature as God and Man so that they are not easily provoked by teachings that are not in accordance with the truth of God's Word contained in the testimony of the Bible. The research method used in this study is the method of literature study or literature-based descriptive qualitative study. With data collection techniques through analyzing the contents of the literature. There are various references in the form of books, online journals, articles and theses. The result of this research is that Jesus Christ is truly true God and true man in His divine and human nature and this is proven in the testimony of the books in the New Testament through New Testament theology.